2014
DOI: 10.1074/jbc.m114.577403
|View full text |Cite
|
Sign up to set email alerts
|

Maturation of Rhizobium leguminosarum Hydrogenase in the Presence of Oxygen Requires the Interaction of the Chaperone HypC and the Scaffolding Protein HupK

Abstract: Background: [NiFe] hydrogenase biosynthesis requires the interaction among multiple accessory proteins for metal cofactor assembly. Results: Combined bioinformatic protein modeling and mutant analysis on HupK and HypC proteins identify key residues required for hydrogenase maturation. Conclusion: HypC-HupK interaction is a relevant step for hydrogenase biosynthesis in the presence of oxygen. Significance: The results expand our knowledge on the mechanism of hydrogenase biosynthesis in aerobic bacteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…HypC-type chaperones have been shown to interact directly with unprocessed large subunits, or large subunit homologues, in a number of bacterial systems (Albareda et al, 2014;Drapal & Böck, 1998;Jones et al, 2004;Winter et al, 2005) and HypC has been proposed to deliver the completed Fe(CN) 2 CO cofactor directly into the active site cavity of the catalytic subunit of Hyd-3 (Magalon & Böck, 2000;Blokesch et al, 2001;Böck et al, 2006). This suggests a highly specific interaction between HypC and HycE.…”
Section: Discussionmentioning
confidence: 99%
“…HypC-type chaperones have been shown to interact directly with unprocessed large subunits, or large subunit homologues, in a number of bacterial systems (Albareda et al, 2014;Drapal & Böck, 1998;Jones et al, 2004;Winter et al, 2005) and HypC has been proposed to deliver the completed Fe(CN) 2 CO cofactor directly into the active site cavity of the catalytic subunit of Hyd-3 (Magalon & Böck, 2000;Blokesch et al, 2001;Böck et al, 2006). This suggests a highly specific interaction between HypC and HycE.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of the HypC protein levels after over-production by immunoblotting revealed that while the HypC (Gstop) and HypC(+ HQL/-GS/Gstop) variants could readily be detected, including possible dimeric forms of the proteins as observed previously Albareda et al, 2014], the HypC(PAD/+ HQL/Gstop) variant could not be detected (online suppl. Fig.…”
Section: Hypc Determinants Important For the Recognition Of Hycementioning
confidence: 93%
“…The R. leguminosarum hyp gene cluster is necessary for the production of a functional uptake [NiFe] hydrogenase system and is controlled by the nitrogen fixation regulatory protein NifA [ 18 , 19 ]. It has been shown that the R. leguminosarum hypA gene is specifically expressed in bacteroids and required for hydrogenase activity and processing [ 20 ], the HypB protein from B. japonicum is required for the nickel-dependent transcriptional regulation of hydrogenase [ 21 ], and HypC and HypD are involved in the synthesis and transfer of the Fe(CN) 2 CO cofactor precursor [ 22 ]. However, the function and mechanism of rhizobial HypE in the symbiotic fixation of nitrogen is not well-established.…”
Section: Introductionmentioning
confidence: 99%